Populism and Protest - Hirschmann, Nancy J. (Frontiers in Sociology, 2021)
The essay considers populism in the present moment in relation to Black Lives Matter as a popular protest movement. Popular protest movements demand that government change; populism in the present moment seeks to act extra-governmentally, and to this end relies on violence in the face of peace protest movement. This violence demonstrates the white patriarchalism of contemporary populism. I argue that peaceful, popular protest is an important tool to resist white patriarchal populist authoritarianism.